Atlas of World War II : History's Greatest Conflict Revealed Through Rare Wartime Maps and New Cartography - Hyslop, Stephen G. 1950- (Stephen Garrison); Kagan, Neil; Rendell, Kenneth W. (Washington, D.C. National Geographic, 2018)
"This atlas delves into the cartographic history of WWII: naval, land, and aerial attacks from the invasion of Poland to Pearl Harbor and the Battle of the Bulge. Rare maps include a detailed Germany & Approaches map used by Allied forces in the final stages of the war, full large-scale wartime maps of the world used by President Roosevelt, and crucial Pacific theater maps used by B-17 pilots. Satellite data renders terrain as never before seen, highlighting countries and continents in stunning detail to include the towns, cities, provinces and transportation roads for a pinpoint-accurate depiction of army movements and alliances. Gripping wartime stories from these hallowed fields of battle, along with photographs, sketches, confidential documents, and artifacts color the rest of this timeless and informative book"--
Prelude to war, 1941: Blitzkrieg -- Prelude to war, 1943: war in the Pacific -- 1942-1944: breaking Hitler's grip -- 1944-1945: victory over Germany -- 1943-1945: defeating Japan.
Includes bibliographical references (page 252) and index.
Keywords: World War, 1939-1945 -- Atlases; World War, 1939-1945 -- Maps -- Campaigns -- Europe; World War, 1939-1945 -- Maps -- Campaigns -- Asia; Europe -- Maps -- History, Military -- 20th century; Asia -- Maps -- History, Military -- 20th century; Atlases